The Path to Ethical and Moral Use of Media Tools in Data Mining for Social Networks (International Journal of Innovative Research in Computer Science & Technology, 2018)
The development of newer and easy to use  ICT applications especially those that allow social  interactions has led to in-creased user levels and  experiences. It amazes to see the young operating a  smart phone with no challenges unlike their parents.  Although these applications have come of age, it is  important to address the moral and ethical issues that  have emanated with these new applications. This paper  addresses moral and ethical issues related to various  applications in ICT. It specifically identities personal  morals and ethics as the main agents of inculcating  moral and ethical behaviors in the development of and  usage of ICT related applications. It discusses the role  played by morals and ethical behavior in ICT, Social  networking sites and tools, and mobile phone  applications (mobile apps). It recognizes the role of  application developers and general users of ICT in  instilling ethical behaviors among themselves and to other remote users. In conclusion, it identifies the  critical roles of all types of users and proposes that all  should be guided by their personal morals and ethical  values that define their characters.
Keywords: Ethics; Morals; Code of Ethics; Enforcement; Policy; Social Media